2004
DOI: 10.1111/j.1752-7325.2004.tb02745.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Handedness Correlates of Recurrent Aphthous Stomatitis in the Turkish Population

Abstract: The present study suggests that left-handedness appears to be a predictor factor for RAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
2
10
2
Order By: Relevance
“…For the associated factors, our findings are in agreement with the association with higher economic level, which was reported by the Turkish population and also in a study conducted in Argentina. 6 , 10 In a study with baseball players in Arizona, lower prevalence has been identified in African-American individuals, also in accordance with our data. 11 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For the associated factors, our findings are in agreement with the association with higher economic level, which was reported by the Turkish population and also in a study conducted in Argentina. 6 , 10 In a study with baseball players in Arizona, lower prevalence has been identified in African-American individuals, also in accordance with our data. 11 …”
Section: Discussionsupporting
confidence: 89%
“…In Turkey, the prevalence was 22.8% (11,360 respondents); in Iran, 25.2% (10,291 respondents); and in Jordan, 37.3% (2,175 respondents). 6 - 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared with other studies, the figure was around the same value. It was reported (25.2%) in Iran (11), (25.5%) in Turkey (12) and 17.7% in Sweden (13) but lower than the prevalence reported in Jordan (78.1%) (2). These variations could be explained due to the fact that in this type of study you depend on patients memory about RAU in his or her life as patients were asked “ have you ever suffered from such a lesion in your life” so this type of study depends mainly on patients recollection of the condition in the past, or probably the patient mix RAU with other type of ulcerations, different methodologies used (whether it is registered when the lesion is present, or it s is done through the clinical history (14), socioeconomic level (15), genetic predisposition, life style of patients and stress (2).…”
Section: Discussionmentioning
confidence: 71%
“…In Iran, the prevalence of RAS is 25.2% (10,291 respondents), in Brazil, 24.9% (2,427 respondents), and in Turkey, 22.8% (11,360 respondents). [12][13][14] In this study, RAS was associated with fruits, vegetables, dairy products and drinking water intake through univariable analysis (p < .05). Other variables, including fried foods, fermented foods, spicy foods, eggs, gender and age, showed no statistically signi cant associations (p ≥ .05).…”
Section: Associations Of Dietary Factors With Rasmentioning
confidence: 67%